2022
DOI: 10.1371/journal.pcbi.1010050
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome-based disease prediction with multimodal variational information bottlenecks

Abstract: Scientific research is shedding light on the interaction of the gut microbiome with the human host and on its role in human health. Existing machine learning methods have shown great potential in discriminating healthy from diseased microbiome states. Most of them leverage shotgun metagenomic sequencing to extract gut microbial species-relative abundances or strain-level markers. Each of these gut microbial profiling modalities showed diagnostic potential when tested separately; however, no existing approach c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
(54 reference statements)
0
23
0
1
Order By: Relevance
“…Similar to previous works ( Grazioli et al , 2022a ; Wu and Goodman, 2018 ), the single-sequence posteriors are modeled as Gaussian distributions with diagonal structure: . By stacking the parameters (represented as column-vectors) and of the latent prior with the and for all available sequences, we define the following two matrices and , where d Z is the dimensionality of the latent single-sequence posteriors: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to previous works ( Grazioli et al , 2022a ; Wu and Goodman, 2018 ), the single-sequence posteriors are modeled as Gaussian distributions with diagonal structure: . By stacking the parameters (represented as column-vectors) and of the latent prior with the and for all available sequences, we define the following two matrices and , where d Z is the dimensionality of the latent single-sequence posteriors: …”
Section: Methodsmentioning
confidence: 99%
“…This allows using stochastic gradient descent to optimize the objective. Various multimodal generalizations of the VIB have been recently proposed: the Multimodal Variational Information Bottleneck (MVIB) ( Grazioli et al , 2022a ) and DeepIMV ( Lee and Schaar, 2021 ). Both MVIB and DeepIMV adopt the PoE to estimate a joint multimodal latent encoding distribution from the unimodal latent encoding distributions.…”
Section: Introductionmentioning
confidence: 99%
“…As presented by Reiman and Dai [61], a bimodal autoencoder can integrate diet and microbial composition to predict the microbial dynamics response to dietary change. Grazioli et al [62] introduce a disease prediction model that relies on the product-of-experts approach to integrate the information from two autoencoders, each expert on a different modality: abundance (species-level) and presence (strain-level) features, respectively.…”
Section: Unveiling Latent Informationmentioning
confidence: 99%
“…Each of the nodes within the shortest path trees is identified as "bottlenecks" [96,97]. There exists a relationship between bottlenecks (high centrality nodes) and essentiality [98][99][100]. It is crucial to note that the same node can function as a bottleneck for multiple shortest path trees.…”
Section: Bottleneckmentioning
confidence: 99%
“…It has been found that betweenness centrality may accurately identify network hub nodes that can enhance the transmission efficiency of data [104]. The betweenness of a protein reveals the protein's potential to facilitate communication among a variety of proteins in the protein networks [98]. Proteins have high betweenness centralities are referred to as key connector proteins with crucial functional and dynamic features [105,106], such as metabolites that regulate the flux between two large metabolic modules.…”
Section: Betweenness Centralitymentioning
confidence: 99%